Driving the Digital Economy: The Role of E-Commerce in Marketing Transformation on TikTok in Indonesia - Pratama, Galih; Firdaus, Firdaus; Juma'i, Juma'i; Febriana, Dita Aulia (Yayasan Riset dan Pengembangan Intelektual, 2025)
This research aims to analyze the role of e-commerce in the digital transformation of marketing with a focus on the TikTok platform in Indonesia. The research uses a quantitative approach with explanatory research methods and involves 100 respondents selected through purposive sampling techniques. The variables studied include customer interaction, personalization, customer experience, and customer behavior. Data were collected through questionnaires and analyzed using the SEM-PLS method on SmartPLS4. The research results show that customer interaction and personalization have a positive and significant impact on customer experience. Additionally, customer experience has a positive and significant impact on customer behavior. Customer interaction also has a positive and significant impact on customer behavior. However, personalization has a positive but not significant impact on customer behavior. This research provides insights into the importance of customer experience in mediating the influence of customer interaction and personalization on customer behavior, as well as serving as a basis for developing more effective digital marketing strategies.